PROBLEMS OF COOPERATION BETWEEN THE UNITS INVOLVED IN THE PROVISION OF EMERGENCY MEDICAL CARE AND WAYS TO OVERCOME THEM (Web of Technology: Multidimensional Research Journal, 2026)
The article analyzes issues of interaction among structures involved in providing medical assistance to the population during emergency situations occurring in peacetime. Existing problems in the management and coordination system are identified, and organizational and managerial mechanisms aimed at addressing these issues are proposed. The results of the study contribute to improving the effectiveness of medical assistance in emergency situations.